The beacon. - Kong, Chong Yew. (2012)
Drawing on the qualities of light, Chong Yew’s photos of resplendent shopping malls capture the spectacle and splendor of our consumeristic culture.The compaction of time and space through the use of long exposures provides a distilled essence of a country where shopping has become the main past time.